High-throughput analysis of the Trypanosoma cruzi minicirculome (mcDNA) unveils structural variation and functional diversity (2024)
Trypanosoma cruzi causes Chagas disease and has a unique extranuclear genome enclosed in a structure called the kinetoplast, which contains circular genomes known as maxi- and minicircles. While the structure and function of maxicircles are well-understood, many aspects of minicircles remain to be discovered. Here, we performed a high-throughput analysis of the minicirculome (mcDNA) in 50 clones isolated from Colombia’s diverse T. cruzi I populations. Results indicate that mcDNA comprises four diverse subpopulations with different structures, lengths, and numbers of interspersed semi-conserved (previously termed ultra-conserved regions mHCV) and hypervariable (mHVPs) regions. Analysis of mcDNA ancestry and inter-clone differentiation indicates the interbreeding of minicircle sequence classes is placed along diverse strains and hosts. These results support evidence of the multiclonal dynamics and random bi-parental segregation. Finally, we disclosed the guide RNA repertoire encoded by mcDNA at a clonal scale, and several attributes of its abundance and function are discussed.